Timberline Studies in Central Mexico - Lauer, Wilhelm (Arctic and Alpine Research, 1978)
The climatology and ecology of the timberline on central Mexican volcanoes is reported. Timberline is defined as the upper limit of more or less closed stands of Pinus hartwegii; it occurs at about 4000 m at a boundary conditioned by cold and dryness (Kältetrockengrenze). Climatological parameters from four stations on Pico de Orizaba are reported including temperature, number of frost-change days, precipitation, and soil moisture. There are approximately 210 frost-change days, 50% of which occur during the winter. Their number rapidly decreases in March/April, at which time spring growth of P. hartwegii begins. Maximum daily temperature fluctuations of 70°C were recorded in dry tufted grass. An asymmetrical arrangement of vegetation belts is evident. Reasons for this are discussed, including climate regimes, soil conditions, and exposure. Both man-made and natural fires have influenced the development of the timberline. Lightning-produced fires occur principally along the upslope portion of the timberline and are naturally contained whereas man-made fires are more frequent, start lower down the mountain, and spread rapidly upward causing a lowering of the timberline. The timberline of central Mexico is characterized as a transition zone and cannot be assigned to a specific climatic zone.